Return Saham Dan Faktor Fundamental Pada Pra Krisis Ekonomi Global 2008 Di Bursa Efek Indonesia - Mohamad Febriawan; Perdana Wahyu Sentosa (Journal of Economics and Business Aseanomics (JEBA), 2018)
This study aimed to analyze the influence of liquidity (Current Ratio), Leverage (Debt to Equity Ratio), Profitability (Net Profit Margin), and Return on Equity (ROE) on the Stock’s Return during pre-crisis of global economy 2008 (subprime mortgage). This study used financial data of emitens which listed at LQ-45 at Indonesia Stock Exchange. The analytical method is pooled cross section (panel) with a significant level of 5%. This study finds that the period of pre-crisis 2008 shows that liquidity, leverage, and profitability have positively effect on stock’s return. In general this study concludes some financial information misleading and conflict of interest that related to exessive risk taking by investors in investment decision without corporate finance and risk policy’s consideration such as liquidity, solvency and asset prices forming in the Indonesia Stock Exchange before september 2008.